Trend, geographical distribution, and determinants of modern contraceptive use among married reproductive-age women, based on the 2000, 2005, 2011, and 2016 Ethiopian demographic and health survey - Teshome Demis Nimani; Zinabu Bekele Tadese; Eyob Eshete Tadese; Fikadu Wake Butta (BMC, 2023)
Abstract Background The most common family planning method is modern contraception. It is a cost-effective way to reduce maternal and neonatal morbidity and mortality and enable women to make informed choices about their reproductive and sexual health. The trend of modern contraceptive utilization has shown drastic change in Ethiopia, and identifying the major factors contributing to such a drastic change is vital to improving plans and strategies for family planning programs. Therefore, this study analyzed the trend, geographical distribution, and determinants of modern contraceptive use among married reproductive-age women in Ethiopia. Method This study used secondary data from the EDHS 2000-2016, collected from a population-based cross-sectional study by the Central Statistical Agency, focusing on married reproductive-age women aged 15-49. The study analyzed the modern contraceptive use trends through descriptive analyses conducted in three phases: 2000-2005, 2005-2011, and 2011-2016. The study utilized bivariable and multivariable logistic regression analyses to identify determinant factors, with significant variables declared using a P-value of 0.05 and an adjusted OR with 95% confidence interval. Analysis was conducted using STATA.14 and R. Spatial analysis was done using ArcGIS version 10.8 and SatScan™ version 9.6. Result A weighted total of 33,478 women are included in the study, with a mean age of 31.4 years (8.6 SD). There was a significant increase in the trend of modern contraceptive use among married women over the study period, from 2000 to 2016, from 7.2% to 2000 to 15.7% in 2005, to 30% in 2011, and to 39.5% in 2016. The maximum increase was seen in the second phase (2005-2011), with a 14.3% increase. Factors like age of respondents, educational status, religion, residence, region, wealth index, number of living children, husbands' desire to have more children, and media exposure were found to be predictors for modern contraceptive utilization. Conclusion The prevalence of modern contraceptive use is below 50%, and there is also evidence of wide geographical variation in modern contraceptive use in Ethiopia. Thus, policymakers, high institutions, and other stakeholders must work collaboratively with the government in order to improve awareness about modern contraceptive use.